Chondrichthyans evolution, diversity and senses. - Boisvert, Catherine; Johnston, Peter; Trinajstic, Kate; Johanson, Zerina (Springer, 2019)
This book will take you on a journey to discover the origin and diversification of the head, which evolved from a seemingly headless chordate ancestor.